Simulating drone and bodily movements: a behavioral study - Kolesnikov, Anna; Calbi, Marta; Montalti, Martina; Langiulli, Nunzio; Guerra, Michele; Gallese, Vittorio; Umiltà, Maria Alessandra (Frontiers in Psychology, 2025)
IntroductionThis study explores how drone movements and human bodily gestures influence spectators’ perceptions, focusing on physical and emotional involvement, aesthetic appreciation, and time perception.MethodsInspired by the iconic staircase scene from the Soviet film The Cranes Are Flying (1957), a set of 81 naturalistic video stimuli was created using a drone-mounted camera, varying in Drone Movement (Ascending, Descending, Still), Human Presence (Female, Male, None), and Image Speed (Normal, Low, Very Slow). Participants evaluated each video based on Liking, Perceived Movement, Physical Involvement, Emotional Involvement and Perceived Duration.Results and discussionResults showed that ascending movements elicited the highest levels of perceived movement, aesthetic appreciation and emotional engagement, outperforming descending and still movements. These results could be explained by a stronger sense of effort and exertion associated with ascending movements, aligning with the embodied simulation of upward motion against gravity. Human presence significantly enhanced ratings across all metrics compared to videos without human figures, thus suggesting that bodily movements play a crucial role in evoking stronger viewer involvement. Additionally, the Female condition received higher aesthetic ratings. Notably, normal image speed yielded greater perceived movement and physical involvement than slowed footage, highlighting a stronger connection to the natural rhythm of bodies in motion. Furthermore, ascending and descending conditions were perceived as lasting longer than still, corroborating prior research on time perception distortions with dynamic stimuli. Correlation analysis highlighted a strong link between physical involvement, emotional engagement, and aesthetic appreciation, underscoring the interplay between bodily and emotional responses. This study emphasizes the potential of drone-based cinematography to evoke embodied and emotional responses, reinforcing the role of embodied simulation theory in cinematic experiences.